Integrasi Manajemen Perilaku dan Keputusan Keuangan dalam Perusahaan: Analisis Literatur Strategi Manajemen - Musa, Chalid Imran (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This research aims to explore the integration of behavioral and financial management in companies and provide strategies to enhance overall corporate performance. The research methodology employed was a literature review and related studies. Qualitative and descriptive approaches were used to analyze the relationship between behavioral and financial management in the organizational context. The findings indicate that effective integration of behavioral and financial management can enhance employee productivity, improve financial decision-making, and foster a strong organizational culture. Strategies required include appropriate recruitment, ongoing employee development, effective communication, behavior-informed financial decision-making, and comprehensive performance evaluation. By implementing these approaches, companies can achieve improved financial performance and fulfill their long-term objectives